2019
DOI: 10.1144/qjegh2018-210
|View full text |Cite
|
Sign up to set email alerts
|

Coastal landslide monitoring at Aldbrough, East Riding of Yorkshire, UK

Abstract: The paper describes results to date of a continuing monitoring study of coastal 'soft cliff' recession at the British Geological Survey's (BGS's) Coastal Landslide Observatory (CLO) on the east coast of England at Aldbrough, East Riding of Yorkshire. The cliffed site, part of the 50 km long Holderness coast, consists of glacial deposits, and is one of the most rapidly eroding coastlines in Europe. This rapid rate of erosion provides an ideal opportunity for observation and process understanding because it faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
2
7
0
2
Order By: Relevance
“…In the second one (November 2019), the FG3 marker registered the largest 3D movement detected for a single campaign, moving 14.06 m in the lapse October-November 2019; also 19 of the 38 markers moved more than 30 cm in one month, reaching four of them (ARB, FF1, FG2, FG1) values equal or higher than 1 m (respectively, 1.70 m, 1.21m, 1.03 m, 1.00 m). The obtained rates, although they are measured on the slope and do not strictly correspond to the cliff retreat, are in line with those obtained by Hobbs et al (2020) on the Holderness coast. The arrows in Fig.…”
Section: Slope Displacement For the Period June 2018 -May 2020: Quantitative Measurements And Relationships With Rainfallsupporting
confidence: 88%
See 2 more Smart Citations
“…In the second one (November 2019), the FG3 marker registered the largest 3D movement detected for a single campaign, moving 14.06 m in the lapse October-November 2019; also 19 of the 38 markers moved more than 30 cm in one month, reaching four of them (ARB, FF1, FG2, FG1) values equal or higher than 1 m (respectively, 1.70 m, 1.21m, 1.03 m, 1.00 m). The obtained rates, although they are measured on the slope and do not strictly correspond to the cliff retreat, are in line with those obtained by Hobbs et al (2020) on the Holderness coast. The arrows in Fig.…”
Section: Slope Displacement For the Period June 2018 -May 2020: Quantitative Measurements And Relationships With Rainfallsupporting
confidence: 88%
“…However, some previous works have obtained average retreat rates of 0.57 m year -1 for the period 2006-2017, reaching rates up to 1.22 and 2.19 m year -1 near the town of Luanco, in the surroundings of Peñas Cape (Domínguez-Cuesta et al, 2020a). Although these retreat values corresponds to specific areas, they are values similar to those obtained in Fisterra, Northern Spanish Atlantic coast (range 0.03 -2.78 m year -1 , Pérez-Alberti et al, 2013), much higher than the established in the central coast of Portugal (range 0.013 -0.130 m year -1 , Epifânio et al, 2013) or the Atlantic rocky coast (Gómez-Pujol et al, 2014 and references therein) and they agree with those reported in Holderness, considered the most active coast in Europe, with values of 2 m year -1 (Bird, 2008;Castedo et al, 2015;Hobbs et al, 2020).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…The use of UAV images for coastal landslide surveying and modeling at the British Geological Survey's "coastal landslide observatory" on the Holderness coast of Yorkshire (Hobbs et al 2020) is shown in Figs. 13 and 14.…”
Section: Examples Of Landslides Studies In the Uk Using Uavmentioning
confidence: 99%
“…The BGS Coastal Landslide Observatory, at Aldbrough, East Riding of Yorkshire, has been monitored since 2001, using a variety of GNSS, TLS, and MMS techniques [24]. The cliff faces northeast, is low (17 m) and of regular height.…”
Section: Monitoring Changementioning
confidence: 99%